Epithelioid inflammatory myofibroblastic sarcoma treated with Alectinib: a case report and literature review - Wu, Xinchun; Zhu, Junxi; Yan, Yichao; Niu, Dongfeng; Chen, Lin (Frontiers in Oncology, 2024)
Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is an extremely rare and aggressive form of inflammatory myofibroblastic tumor. Clinically, it has a high risk of relapse and peripheral organ infiltration, and it responds poorly to conventional chemotherapy. Anaplastic lymphoma kinase (ALK) inhibitors are currently the most effective targeted therapy for EIMS. This report discusses a typical case of abdominal EIMS in a 43-year-old woman. The tumors recurred rapidly within one month after surgery. Alectinib was promptly administered upon diagnosis. However, the patient developed a severe allergic reaction to the medication. After a comprehensive assessment and symptomatic treatment, her condition stabilized, leading to a favorable prognosis. This study summarizes cases of abdominal EIMS, highlights the successful use of Alectinib for treatment, and discusses the management of medication-related complications.